2004
DOI: 10.1016/j.pain.2004.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Depression increases onset of tension-type headache following laboratory stress

Abstract: The aim of this study is to examine the influence of depression on headache onset following laboratory stress and on psychophysiological variables associated with tension-type headaches (TTHs). Diagnostic interviews identified three groups: headache prone and depressed (HP/D, N = 13); headache prone not depressed (HP/ND, N = 22); and healthy controls (HC, N = 13). Ss completed a laboratory stress task. Blind evaluations of pericranial muscle tenderness (PMT) and pressure pain thresholds (PPT) were obtained imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 55 publications
3
47
0
1
Order By: Relevance
“…Moreover, behavioral and psychologic therapies have been shown to be effective for the treatment of TTH [11•]. Janke et al [12] demonstrated that depression increased vulnerability to TTH in patients with frequent headaches during and following the laboratory stress test and was associated with elevated pericranial muscle tenderness. It was suggested that anxiety and depression may contribute to increased excitability in central nociceptive pathways in patients with CTTH [12,13].…”
Section: Emotional Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, behavioral and psychologic therapies have been shown to be effective for the treatment of TTH [11•]. Janke et al [12] demonstrated that depression increased vulnerability to TTH in patients with frequent headaches during and following the laboratory stress test and was associated with elevated pericranial muscle tenderness. It was suggested that anxiety and depression may contribute to increased excitability in central nociceptive pathways in patients with CTTH [12,13].…”
Section: Emotional Factorsmentioning
confidence: 99%
“…Janke et al [12] demonstrated that depression increased vulnerability to TTH in patients with frequent headaches during and following the laboratory stress test and was associated with elevated pericranial muscle tenderness. It was suggested that anxiety and depression may contribute to increased excitability in central nociceptive pathways in patients with CTTH [12,13]. The neurobiologic mechanisms through which emotional factors promote TTH are unknown and further studies are needed to explore the possible relation of corticolimbic circuits to sensitization of nociceptive pathways in TTH.…”
Section: Emotional Factorsmentioning
confidence: 99%
“…Anxiety or depression may contribute to the sensitization of pain transmission circuits [12,18]. For example, depression was associated with elevations in pericranial muscle tenderness, reductions in peripheral pain tolerance, and an increased likelihood that patients would experience tension-type headaches after laboratory psychologic stress [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, depression was associated with elevations in pericranial muscle tenderness, reductions in peripheral pain tolerance, and an increased likelihood that patients would experience tension-type headaches after laboratory psychologic stress [18]. Thus, depression or anxiety may increase vulnerability to or maintain frequent tension-type headaches by aggravating the central sensitization in pain transmission pathways, and through associated muscle tension that elevates peripheral input.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CTTH also have higher rates of catastrophizing and avoidance [9••]. Depression and anxiety may contribute to the already existing disorder in patients with CTTH, causing a decreased threshold for pain and a higher frequency of headache [10]. The severity of headache also increases signifi cantly with higher frequency [6].…”
Section: Introductionmentioning
confidence: 99%